Internationalization and Quality From the Perspectives of Stakeholders in the English and Turkish Higher Education Sectors. Issue 3 (2nd October 2022) - Ozer, Omer
Abstract: This cross-national comparative study examined "internationalization" and "quality" in the English and Turkish higher education (HE) sectors, thereby presenting a comparative discussion of the state of HE in the two countries. Using a phenomenological approach, the study generated qualitative and quantitative data from different sources. The findings suggest that all stakeholder groups largely understand internationalization and quality similarly; however, there were marked differences in the obstacles to internationalization and quality management.